Fatigue analysis of welded joints - Lim, Jonathan Chung Ying (2019)
Welding is an extensively used metal joining technique across many manufacturing industries, and fatigue failure is one of the most common forms of mechanical failures in welded joints. Hence, it is important to understand the fatigue properties of welded joints and to be able to accurately predict fatigue lifespans. This project focuses on the fatigue properties of cruciform welded joints, and investigates the influence of grinding weld toes on the fatigue lifespan of cruciform welded joints. Axial load fatigue testing was carried out on cruciform steel welded joint specimens of different grinded weld toe radiuses, to assess the influence of weld toe grinding on improving fatigue lifespan. ABAQUS software was used to carry out Extended Finite Element Method (XFEM) simulation to obtain stress intensity factors (SIF). The effects of crack aspect ratio and crack depth on the SIF and fatigue lifespan were investigated. The SIF solutions obtained were used to predict fatigue lifespan and were compared with the experimental fatigue lifespan results. XFEM automated crack growth on ABAQUS was also explored in this study.